To solve the equation using inverse operations, we need to isolate the variable v.
First, we can subtract 11/3 from both sides of the equation:
v + 11/3 - 11/3 = 1/3 - 11/3
This simplifies to:
v = -10/3
Therefore, the solution to the equation is v = -10/3.
Solve using inverse operations. v+11/3=1/3
3 answers
is it the right answer ?
Apologies for the mistake in my previous response.
To solve the equation using inverse operations, we want to isolate the variable v by undoing the operations that have been done to it.
The equation is v + 11/3 = 1/3.
First, we need to undo the addition of 11/3 to v. To do this, we will subtract 11/3 from both sides of the equation:
v + 11/3 - 11/3 = 1/3 - 11/3
This simplifies to:
v = -10/3
So the correct solution to the equation v + 11/3 = 1/3 is v = -10/3. Apologies for the confusion caused.
To solve the equation using inverse operations, we want to isolate the variable v by undoing the operations that have been done to it.
The equation is v + 11/3 = 1/3.
First, we need to undo the addition of 11/3 to v. To do this, we will subtract 11/3 from both sides of the equation:
v + 11/3 - 11/3 = 1/3 - 11/3
This simplifies to:
v = -10/3
So the correct solution to the equation v + 11/3 = 1/3 is v = -10/3. Apologies for the confusion caused.